Distributed and Parallel Architectures for Spatial Data - Belussi, Alberto; Migliorini, Sara; Carra, Damiano; Clementini, Eliseo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book aims at promoting new and innovative studies, proposing new architectures or innovative evolutions of existing ones, and illustrating experiments on current technologies in order to improve the efficiency and effectiveness of distributed and cluster systems when they deal with spatiotemporal data.